2000
DOI: 10.1108/02652320010322976
|View full text |Cite
|
Sign up to set email alerts
|

Market segmentation in the Indonesian banking sector: the relationship between demographics and desired customer benefits

Abstract: The recent economic turmoil in Indonesia has hit the financial service sector hard. Consumer confidence in banks is low and institutions are having to work harder than ever to recruit and retain their customers. In this article the potential for banks to utilize benefit segmentation to assist them in this context is explored. It will be argued that for benefit segmentation to offer any real utility in this context, a link must be found between benefits and general observable characteristics, such as demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 50 publications
0
57
0
1
Order By: Relevance
“…As suggested by Hair et al, (1995), seven factors were identified for the factor analysis using the eigen value criteria that suggest extracting factors with an eigenvalue of greater than 1.0. In conducting the factor analysis we followed Hair et al (1995) and Alfansi and Sargeant (2000). The seven factors identified explain 59.21 percent of the total variance.…”
Section: Test For Construct Validity: Factor Analysismentioning
confidence: 99%
“…As suggested by Hair et al, (1995), seven factors were identified for the factor analysis using the eigen value criteria that suggest extracting factors with an eigenvalue of greater than 1.0. In conducting the factor analysis we followed Hair et al (1995) and Alfansi and Sargeant (2000). The seven factors identified explain 59.21 percent of the total variance.…”
Section: Test For Construct Validity: Factor Analysismentioning
confidence: 99%
“…In conducting the factor analysis we followed Hair et al (1995) and Alfansi and Sargeant (2000). The rotated factor matrix is displayed in Table 3.…”
Section: Test For Content and Construct Validity Of The Studymentioning
confidence: 99%
“…As suggested by Hair et al, (1995), six factors were identified for the factor analysis using the eigen value criteria that suggest extracting factors with an eigenvalue of greater than 1.0. In conducting the factor analysis we followed Hair et al (1995) and Alfansi and Sargeant (2000). The rotated factor matrix is displayed in Table II.…”
Section: Test For Construct Validity: Factor Analysismentioning
confidence: 99%